The effect of (-)-epigallocatechin 3-O--gallate in vitro and in vivo in Leishmania braziliensis: involvement of reactive oxygen species as a mechanism of action. - Job D F Inacio; Luiza Gervazoni; Marilene M Canto-Cavalheiro; Elmo E Almeida-Amaral (Public Library of Science (PLoS), 2014)
Leishmaniasis is a parasitic disease associated with extensive mortality and morbidity. The treatment for leishmaniasis is currently based on pentavalent antimonials and amphotericin B; however, these drugs result in numerous adverse side effects. Natural compounds have been used as novel treatments for parasitic diseases. In this paper, we evaluated the effect of (-)-epigallocatechin 3-O-gallate (EGCG) on Leishmania braziliensis in vitro and in vivo and described the mechanism of EGCG action against L. braziliensis promastigotes and intracellular amastigotes.In vitro activity and reactive oxygen species (ROS) measurements were determined during the promastigote and intracellular amastigote life stages. The effect of EGCG on mitochondrial membrane potential (ΔΨm) was assayed using JC-1, and intracellular ATP concentrations were measured using a luciferin-luciferase system. The in vivo experiments were performed in infected BALB/c mice orally treated with EGCG. EGCG reduced promastigote viability and the infection index in a time- and dose-dependent manner, with IC50 values of 278.8 µM and 3.4 µM, respectively, at 72 h and a selectivity index of 149.5. In addition, EGCG induced ROS production in the promastigote and intracellular amastigote, and the effects were reversed by polyethylene glycol (PEG)-catalase. Additionally, EGCG reduced ΔΨm, thereby decreasing intracellular ATP concentrations in promastigotes. Furthermore, EGCG treatment was also effective in vivo, demonstrating oral bioavailability and reduced parasitic loads without altering serological toxicity markers.In conclusion, our study demonstrates the leishmanicidal effects of EGCG against the two forms of L. braziliensis, the promastigote and amastigote. In addition, EGCG promotes ROS production as a part of its mechanism of action, resulting in decreased ΔΨm and reduced intracellular ATP concentrations. These actions ultimately culminate in parasite death. Furthermore, our data suggest that EGCG is orally effective in the treatment of L. braziliensis-infected BALB/c mice without altering serological toxicity markers.